P-20 Education Policy: School to College Transition Policy in Washington State - Pitre, Paul E (Education Policy Analysis Archives, 2011)
This study examines Washington State’s attempt to move toward an integrated, P-20 system of education that enhances student transitions from high school to college. In analyzing Washington as a single case study, a profile of the state is developed on key access related characteristics. Data for this study were gathered utilizing fundamental case study methods. In depth qualitative interviews were conducted with Washington State Legislators, legislative staff, key state education agency officials, and college and university representatives. Document analyses of agency records, public hearings, testimonies, position papers, reports, and public meeting records were also conducted. This study found that Washington has many key programs in place to enhance student transitions between the K-12 system and the higher education, but the state’s current approach lacks coherence and cohesion. This study also found that the state has developed a new and innovative model with the potential to solve many transition related issues, but it will require assessment to determine its actual effectiveness.